Analisis Pembentukan Portofolio Optimal Saham-Saham Big Bank di LQ-45 Menggunakan Model Elton dan Gruber di Bursa Efek Indonesia Periode 2019-2023 - Friska Monika Sari Siagian; Muhammad Richo Rianto; Jhonni Sinaga; Adler Haymans Manurung (Yayasan Inovasi Akademi Nusantara, 2025)
Analysis of Optimal Portfolio Formation of Big Bank Stocks in LQ-45 Using the Elton and Gruber Model on the Indonesia Stock Exchange for the 2019-2023 Period. This study aims to analyze the management of stock portfolios on the Indonesia Stock Exchange using the Elton and Gruber Model, focusing on Big Bank stocks included in the LQ-45 stock index during the 2019-2023 period. This study uses monthly data for the 2019-2023 period, with data analysis techniques using Microsoft Excel. The results of this study found that there were 3 stocks included in the optimal portfolio with an Excess Return to Beta (ERB) value greater than the Cut-Off Rate (CI), namely; Bank Central Asia Tbk (BBCA), Bank Rakyat Indonesia Persero (BBRI) and Bank Mandiri (Persero) Tbk (BMRI). The results show that the optimal portfolio is formed by stocks that have high returns at relatively the same risk level.